Diet evolution in Tropiduridae lizards: ecological relations and phenotypic associations - Fernandes, Danilo Camargo (2024)
Currently, there are over 11,000 described species of Squamata, and an immense ecological variability is observed among lizards from different families, which is usually associated with morphological diversity. Diet, in particular, is an extremely diversified characteristic among different Squamata families. While some groups exhibit less varied feeding habits, such as Gekkota species that are almost exclusively insectivores, other families, like Liolaemidae, show high diversity in diet types, comprising from strictly insectivorous to strictly herbivorous species. This distinction among Squamata families motivated us to conduct an in-depth investigation into the evolution of diet in the Tropiduridae family, a group of neotropical lizards known for its abundance of ecological and natural history data. This allowed us to compile extensive data, classifying 39 species according to their diets and reconstructing the evolution of this trait in the family (chapter 1). We observed significant dietary diversity in Tropiduridae, including insectivorous and omnivorous species, with remarkable variation in the quantity of plants and hard prey consumed among species and also among populations of the same species. We demonstrated that diet is an evolutionarily labile trait in Tropiduridae, having a low phylogenetic signal and our ancestral reconstructions indicate numerous evolutionary transitions, mostly from insectivores to omnivores. Furthermore, we tested for associations between diet and morphology in the family and identified patterns that diverge from other lizard groups: first, we did not detect associations between diet and body size, and omnivorous species comprise larger morphological disparity in the head, with smaller heads overall. Head morphology is associated with the relative amount of hard prey consumed by omnivores, a pattern not detected in insectivores. To explore possible developmental mechanisms involved in the association between head morphology and diet, we performed a controlled experiment using individuals of an omnivorous species, Tropidurus catalanensis, in which we fed animals with different diets from birth (chapter 2). Our results do not support phenotypic plasticity in response to diet in T. catalanensis. Finite element analysis revealed that lizards from the group with a specialised diet typical of wild juveniles exhibited more robust jaws capable of withstanding greater mechanical stress. This contradicts our predictions of better food processing in individuals who had consumed more hard prey or plants during ontogeny. These findings highlight the complexity of the interactions between diet, morphology, and ontogeny in lizards from the Tropiduridae family.